The Effectiveness of Breast Care on Smooth Breast Milk Production in Postpartum Mothers - Syakila Narayana (International Journal of Nursing and Midwifery Research, 2026)
Breast milk is the most important source of nutrition for infants and plays a crucial role in supporting growth, development, and immunity during the early stages of life. However, many postpartum mothers experience difficulties in producing sufficient breast milk, especially during the early postpartum period. Problems such as delayed milk production, breast engorgement, and inadequate stimulation of the breast can interfere with the breastfeeding process. One of the non-pharmacological interventions that can help improve breast milk production is breast care. This study aimed to analyze the effectiveness of breast care on smooth breast milk production in postpartum mothers. This research used a quantitative approach with a quasi-experimental design using a one-group pretest–posttest method. The study was conducted at a maternal health service facility and involved 30 postpartum mothers selected using purposive sampling. Data were collected using observation sheets to assess indicators of breast milk production before and after the breast care intervention. The collected data were analyzed using descriptive statistics and the Wilcoxon signed-rank test to determine the significance of the intervention. The results showed that before the breast care intervention, the majority of respondents (70%) experienced unsmooth breast milk production, while after the intervention, most respondents (76.7%) experienced smooth breast milk production. Statistical analysis showed a significant difference between pretest and posttest results (p = 0.001). In conclusion, breast care is effective in improving smooth breast milk production in postpartum mothers. Therefore, health workers are encouraged to provide education and guidance on breast care practices to support successful breastfeeding.